Strabono Geografijos įžangos: mokslinio diskurso tąsa ir originalumas - Juchnevičienė, Nijolė (Literatūra, 2008)
The so called two prefaces of Strabo’s Geography (books I–II) demonstrably attest that geography as a literary (narrative rather than descriptive) genre has experienced a formative impact of the historiographic tradition. In fact, the two prose genres mentioned have common origin. The very first known histories are also the first known geographies: the works by Hecataeus and Herodotus were without doubt regarded as history, but they are also known as the first extant descriptions of oikoumene. The idea of special book on geography is witnessed for the first time in historiographic tradition, – it belongs to the IVth century historian Ephorus. The role of geography in historical research and the self-importance of geographical studies was first conceptualized by historians such as Ephorus, Polybius or Diodorus. Geography took over from history the main elements of narrative as well as the idea of the prooimion as a methodic programme of the research. The traditional topic of historiographicprooimion is also exploited by Strabo; but his Geography differs from the common historiographic context in its shift to academism and in Strabo’s strive to avoid the “familiarity” of the historiographic discourse. Instead of his, as the author’s, intellectual „biography“, he chooses to present the intellectual “biography” of geography and to define the place of his Geography in it. This attitude has no analogue in historiographic tradition, but without any doubt it originates in the striving of history to discuss its “scientific” nature in the prooimia.